Halal brand quality and halal food purchasing intention among university students: The moderating effect of customer-employee interactions - Ismail Juma Ismail (Social Sciences and Humanities Open)
As customer preferences pivot towards ethical considerations, the landscape of consumption among customers has witnessed a notable shift towards products aligned with culture, beliefs, and moral values. Thus, halal food products have emerged as significant solutions within this evolving paradigm. This encourages customers to develop perceived ethical choices. Therefore, this study delves into the predictive role of the halal brand perceived quality (HBPQ) on halal food product purchase intentions when moderated by customers' perceived interaction with employees among university students. The study employed a sample of 288 university students in Tanzania as potential customers of halal food products, selected using a purposive sampling technique. During the process, an online questionnaire disseminated through Google Forms was used to solicit the investigation of the interplay between halal brand perceived quality, halal food product purchase intentions, and customers' perceived interaction with employees. The findings of this study reveal compelling insights that HBPQ positively and significantly influences students' intention to purchase halal food products. Second, the findings reveal that customers' perceived interaction with employees is a significant factor influencing halal food product purchase intentions among university students. Finally, the study's findings reveal that the relationship between halal brands' perceived quality and halal food purchase intention is positively and significantly moderated by customers' perceived interaction with employees.